Effect of behavior-specific praise on student on-task behavior in career and technical education - Hogg, Jennifer A.; Royer, David James; Newton, Nicholas A.; Priddy, Amber (Frontiers in Education, 2024)
Behavior-specific praise (BSP) is a low-intensity strategy used to reinforce positive behaviors, including student academic engagement in school settings. In this study, we leveraged a single training on BSP for a career and technical education (CTE) teacher in a suburban Southeast high school to determine effects on student on-task behavior. Using an A-B-A-B withdrawal design, we observed the teacher’s rate of general praise and BSP statements, and the percentage of 1-min momentary time sampling intervals with on-task behavior of four high school students. The general education CTE teacher increased his rate of BSP, and all four students increased on-task behavior during intervention phases. Social validity questionnaires identified a positive impression from students and teacher about implementing BSP in the classroom. Limitations and future directions are discussed.